Web-Based Abulyatama Alumni Information System - Ardiansyah, Teuku Muhammad (Lembaga KITA, 2021)
Tracer study is a study of tracer traces of graduates or alumni carried out to alumni after graduation. The obstacle faced by STMIK Abulyatama in conducting a tracer study is at the time of data collection, currently collecting data manually by distributing questionnaires and telephone interviews with alumni and companies. Therefore, it is necessary to develop a complete E-Tracer study service, which can provide information for higher education institutions for the benefit of curriculum improvements, trace alumni in detail and determine user satisfaction of college graduates. The research objectives are; (1) To find out the alumni information system using a web-based programming language, (2) Designing an alumni management information system using Data Flow Diagrams (DAD) and programming languages ​​such as HTML, CSS, JQuery, JSON, PHP and MySQL as databases, and (3) To improve the existing system to be even better, by building an information system that can improve performance on alumni data collection at Abulyatama University. The stages in the research consist of; literature study, data collection, systems analysis, system development, and report generation. Based on the results of the alumni information system analysis, it can be seen that until now it is still done manually. The author can conclude several things, namely; (1) With a Web-Based Alumni Information System, it is hoped that it will make work easier and accurate and more time-efficient information can be obtained, (2) The use of a manual system has limitations in the data search process, because the data is still stored in archive form, ( 3) Difficulty in updating the latest data for publication to the public, and (4) With this application, it is expected to simplify and speed up the administrative process at Abulyatama University.